A descriptive survey of renal unit practitioners' knowledge, attitude and practice relative to use and effects of unfractionated heparin in selected adult chronic haemodialysis centres in the Cape Town metropole - Ockhuis, Debra (Division of Nursing and Midwifery, 2015)
Background: Chronic haemodialysis treatment of 3-4 hours' duration two or three times a week is the most common renal replacement therapy for adult patients diagnosed with stage 5 end-stage kidney failure. During the procedure 200-250 ml/minute of the patient's blood volume is extracorporeal and patency of the circuit is maintained by an anticoagulant, for example, unfractionated heparin (UFH). Incorrect dosage or time of administration of UFH can have serious adverse effects if not fatal consequences for patients. It is important to perform base-line clotting studies before the initial administration and subsequent doses of UFH. There is a paucity of published information on renal unit practitioners' knowledge, attitude and practice (KAP) concerning the administration of UFH globally and no published South African studies were located. Aim: To describe renal unit practitioners' self-reported KAP regarding use and effects of UFH in purposively selected adult chronic haemodialysis centres in the Cape Town Metropole. Secondly, to determine whether there is an association between KAP regarding the use and effects of unfractionated heparin and selected variables (category of renal unit practitioner, years of experience, duration of orientation to the adult chronic haemodialysis unit and in-service education on the pharmacology of UFH).